Noncommutative fluid dynamics in the Snyder space-time - Abdalla, M. C. B. [UNESP]; Holender, L.; Santos, M. A.; Vancea, I. V. (Amer Physical Soc, 2012)
In this paper, we construct for the first time the noncommutative fluid with the deformed Poincare invariance. To this end, the realization formalism of the noncommutative spaces is employed and the results are particularized to the Snyder space. The noncommutative fluid generalizes the fluid model in the action functional formulation to the noncommutative space. The fluid equations of motion and the conserved energy-momentum tensor are obtained.